Massive Spontaneous Hemothorax, Giant Intrathoracic Meningocele, and Kyphoscoliosis in Neurofibromatosis Type 1 - Yusuf, Ayodeji Salman (Medknow Publications & Media Pvt Ltd, 2014)
Neurofibromatosis type 1 (NF-1) is a heterogeneous autosomal dominant disease with an incidence ranging from 1 in 2500 to 1 in 3000. Rare intrathoracic vascular disorders resulting in massive spontaneous hemothorax with fatal consequences may occur in these patients, so also are various types of skeletal dysplasia which may result in dramatic presentations, posing management challenges to the attending physicians. We report the case of a 43-year-old woman with NF-1 who developed spontaneous massive hemothorax and was discovered to have a concurrent giant intrathoracic meningocele and thoracic kyphoscoliosis with severe vertebral dysplastic changes. Surgical treatment via a right thoracotomy with primary repair of the meningocele and spinal fusion with fibula graft resulted in good outcome. This case represents an extreme manifestation of this otherwise indolent disease in clinical practice.